Identification of a silencing element in the human 15q11-q13 imprinting center by using transgenic Drosophila - Lyko, Frank (The National Academy of Sciences, 1998)
Prader–Willi syndrome (PWS) and Angelman syndrome are neurogenetic disorders caused by the lack of a paternal or a maternal contribution from human chromosome 15q11-q13, respectively. Deletions in the transcription unit of the imprinted SNRPN gene have been found in patients who have PWS or Angelman syndrome because of a parental imprint switch failure in this chromosomal domain. It has been suggested that the SNRPN exon 1 region, which is deleted in the PWS patients, contains an imprint switch element from which the maternal and paternal epigenotypes of the 15q11-q13 domain originate. Using the model organism Drosophila, we show here that a fragment from this region can function as a silencer in transgenic flies. Repression was detected specifically from this element and could not be observed with control human sequences. Additional experiments allowed the delineation of the silencer to a fragment of 215 bp containing the SNRPN promoter region. These results provide an additional link between genomic imprinting and an evolutionary conserved silencing mechanism. We suggest that the identified element participates in the long range regulation of the imprinted 15q11-q13 domain or locally represses SNRPN expression from the maternal allele.